Study on the mechanical properties of brazing of Inconel 718 with pre-sintered preforms (PSP, AMS 4777) - Liew, Yin Fei (2018)
This paper examines the effect of holding time on the mechanical properties and microstructure of brazed joints of Inconel 718 and BNi-2 at 1035ºC. The holding time for the specimens ranged from 2 minutes to 10 hours. Tensile test results show that the strength of the bonds increases for a longer holding time to a maximum of 369.51 MPa for a dwell time of 5 hours due to the reduction of deleterious intermetallic phases formed until the effect of increased grain size to 36.5μm diameter in the braze alloy at 10 hour holding time, caused dislocations to slip more easily. SEM analysis of the surface of fracture shows that fracture occurred mainly by brittle failure for specimens with holding time up to 30 minutes and quasi-cleavage fracture for dwell time of 1 hour onwards, showing increased ductility. Fracture surfaces on all specimens show evidence of microcracks which leads to final fracture. The peak of hardness was found to be 614.3HV for the specimen held at 15 minutes due to the formation of hard and brittle intermetallic phases. A precipitation zone at the base metal, in the diffusion affected zone near the boundary was also found. The hardness values in this zone averaged to be 338.75HV, which is higher as compared to as received base metal. The results from EBSD shows evidence of a two-stage melting process due to excess boron freed up in the later stages of melting.